Assessment of the gut bacterial microbiome and metabolome of girls and women with Rett Syndrome. - Santosh Thapa (Public Library of Science (PLoS), 2021)
Background Gastrointestinal problems affect the health and quality of life of individuals with Rett syndrome (RTT) and pose a medical hardship for their caregivers. We hypothesized that the variability in the RTT phenotype contributes to the dysbiosis of the gut microbiome and metabolome in RTT, predisposing these individuals to gastrointestinal dysfunction. Objectives We characterized the gut bacterial microbiome and metabolome in girls and young women with RTT (n = 44) and unaffected controls (n = 21), and examined the relation between the composition of the microbiome and variations in the RTT phenotype. Methods Demographics and clinical information, including growth and anthropometric measurements, pubertal status, symptoms, clinical severity score, bowel movement, medication use, and dietary intakes were collected from the participants. Fecal samples were collected for analysis of the gut microbiome using Illumina MiSeq-based next-generation sequencing of the 16S rRNA gene followed by bioinformatics analysis of microbial composition, diversity, and community structure. Selected end-products of microbial protein metabolism were characterized by liquid chromatography-mass spectrometry. Results The gut bacterial microbiome differed within the RTT cohort based on pubertal status (p<0.02) and clinical severity scores (p<0.02) of the individuals and the type of diet (p<0.01) consumed. Although the composition of the gut microbiome did not differ between RTT and unaffected individuals, concentrations of protein end-products of the gut bacterial metabolome, including γ-aminobutyric acid (GABA) (p<0.001), tyrosine (p<0.02), and glutamate (p<0.06), were lower in the RTT cohort. Differences in the microbiome within RTT groups, based on symptomatic anxiety, hyperventilation, abdominal distention, or changes in stool frequency and consistency, were not detected. Conclusions Although variability in the RTT phenotype contributes to the dysbiosis of the gut microbiome, we presently cannot infer causality between gut bacterial dysbiosis and gastrointestinal dysfunction. Nevertheless, alterations in the gut metabolome may provide clues to the pathophysiology of gastrointestinal problems in RTT.